Acomparative study of the effect of Cisplatin and Albendazole in the Echinococcosis infection in vivo and in vitro and study of the associated histological changes - Muslem Abd-Al Rhman (University of Thi-Qar Journal of Science, 2019)
The present study is included evalution activity cisplatine and albendazole in killing of protoscolices isolation from sheep liver In vitro, also studying pathogenic effects on the liver and kidney and activity ofthem on hydatid cyst number. Also this study improved capability of cisplatin and albendazole to enter thehydatid cyst.This study appeared that cisplatin has ahigh activity in killing of protoscolices In Vitro which reached forpercentage (51.8 , 92.8) % after (1,2) weeks subsequently in concentration ( 1 mg / ml ) in compared withAlbendazole drug which reached for percentage ( 26.2 , 54.2 ) % when used it in the same concentration .The mice when inoculated with 1500 protoscolices in peritoneum and dosage by cisplatin and albendazoleeach one alone after (1,2, 3,4) months from infection.The cisplatin caused decrease in hydatid cyst number which it isolated from infected mice in contrast withthe mice treatment with Albendazole which appeared number of hydatid cyst near from control group.The histological change in liver of mice treatmented with cisplatin appeared variation in inflammationresponse but it was less in compared with control group. The infected mice which treated with Albendazoleappeared high inflammation response.The histological effects on the kidney which it was bleeding and necrosis in urinary tubules and the effectsand change on the kidney increase with progress infection period.